2015
DOI: 10.5792/ksrr.2015.27.3.173
|View full text |Cite
|
Sign up to set email alerts
|

Significant Incidence of Extra-Articular Tibia Vara Affects Radiological Outcome of Total Knee Arthroplasty

Abstract: PurposeTo identify and quantify the presence of extra-articular tibia vara that might influence the mechanical axis alignment after total knee arthroplasty (TKA).Materials and MethodsA total of 48 TKAs in 30 osteoarthritic Indian patients were prospectively evaluated. The hip-knee-ankle angle (HKA), joint line convergence angle, and varus angulation at the femur and tibia were measured from the preoperative and postoperative standing hip-to-ankle radiographs. Four different methods were used to measure the var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 24 publications
1
13
0
Order By: Relevance
“…The MA technique for primary TKA leads to improved implant durability and patient function because it has good radiographic alignment and few axis outliers. [ 20 , 21 ] However, a study of clinical and radiographic outcomes in 280 patients who underwent primary TKA reported that placement of the prosthesis within 3° of varus or valgus did not improve the Kaplan-Meier 15-year survivorship estimates compared with placement of the prosthesis outside of this range. [ 22 ] Theoretically, the KA technique should provide better clinical results than the MA technique in primary TKA because the KA technique reproduces the obliquity and location of the pre-arthritic joint line, which may lead to improvements in clinical outcomes, greater flexion ROM, and increased patient satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…The MA technique for primary TKA leads to improved implant durability and patient function because it has good radiographic alignment and few axis outliers. [ 20 , 21 ] However, a study of clinical and radiographic outcomes in 280 patients who underwent primary TKA reported that placement of the prosthesis within 3° of varus or valgus did not improve the Kaplan-Meier 15-year survivorship estimates compared with placement of the prosthesis outside of this range. [ 22 ] Theoretically, the KA technique should provide better clinical results than the MA technique in primary TKA because the KA technique reproduces the obliquity and location of the pre-arthritic joint line, which may lead to improvements in clinical outcomes, greater flexion ROM, and increased patient satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…[20,21] However, a study of clinical and radiographic outcomes in 280 patients who underwent primary TKA reported that placement of the prosthesis within 3°o f varus or valgus did not improve the Kaplan-Meier 15-year survivorship estimates compared with placement of the prosthesis outside of this range. [22] Theoretically, the KA technique should provide better clinical results than the MA technique in primary TKA because the KA technique reproduces the obliquity and location of the pre-arthritic joint line, which may lead to improvements in clinical outcomes, greater flexion ROM, and increased patient satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…23 A postoperative HKA that deviates more than 3 from neutral correlates with worse functional outcome and prosthesis survival. 24 Saibaba et al 6 have reported that extraarticular tibia vara measured by MDA is associated with abnormal postoperative HKA (beyond 180 + 3 ) when MDA is above 4 with a sensitivity of 78.1%, specificity of 62.5%, and p value of 0.03. This was why our study divided MDA by 4 .…”
Section: Discussionmentioning
confidence: 99%
“…Because Saibaba et al have reported that MDA above 4 was associated with abnormal postoperative HKA. 6 Preoperative and postoperative alignment were assessed by measuring HKA in preoperative and postoperative standing lower extremity view, respectively. HKA was defined as the angle created between the mechanical axis of the femur and the mechanical axis of the tibia (Figure 2 There were positive correlations between preoperative HKA and postoperative HKA in overall cases (p ¼ 0.001, r ¼ 0.187; Table 3).…”
mentioning
confidence: 99%